Dysfunctional Activated Protein C (PC Cádiz) in a Patient with Thrombotic Disease - Sala, N; Borrell, M; Bauer, K A; Viganò-D’Angelo, S; Fontcuberta, J; Félez, J; Rutllant, M L (Thrombosis and Haemostasis, 1987)
The partial characterization of a dysfunctional protein C (PC), provisionally named “PC Cádiz”, in a 45-year-old male patient suffering from recurrent venous thrombosis is described. The only defect found in laboratory assays for haemostasis and hepatic function was a half normal level of both amidolytic and anticoagulant protein C activity, measured by different functional assays that use thrombin-thrombomodulin complex and a snake venom to activate protein C. Protein C antigen was always found to be within normal levels. Two young daughters of the propositus were found to have the same defect. Double-crossed immunoelectrophoresis, performed in the presence and absence of Ca2+ in the first dimension, showed no clear differences between patient and control PC. PC adsorption to barium salts was also found to be normal. Measurement of the PC activation peptide in the barium citrate eluates after PC activation showed no significant differences between patient and 10 normal controls, the concentration of this peptide being very similar to that of PC zymogen in the same eluates before PC activation. These results indicate that this abnormal PC is able to be normally activated by thrombin-thrombomodulin complex but does not exhibit serine protease activity, probably due to a defect in the PC molecule near the active site center.
Keywords: Dysfunctional protein C; PC activation peptide; Venous thrombosis